Fisheries Crime Law Enforcement In Criminal Justice - Strategy, Handling; Akkub, M. Shukri; Alma, Manuputty; Patitinggi, Farida (IJRDO-Journal of Applied Science, 2015)
This study aimed to law enforcement in criminal acts in the field of fisheries in the province of Maluku study was conducted in the province of Maluku, especially Ambon, Maluku Tenggara, Fishing in the Old Court and Court Fishing in Ambon. The data collected consisted of data that is primary and which is secondary. Primary data is data obtained directly from the source data in the field (field research). Primary data were obtained using questionnaires, interviews and document study. Data were analyzed by qualitative analysis through the presentation of data in table form. The results showed in achieving law enforcement strategies in the prevention and eradication of fishing can be done in different ways: criminal policy, integrated fishing industry, improvement of the licensing system, revamping surveillance system, institutionalization of community, networking and the development of the judicial system of fisheries. This can be accomplished with the support of a third operation of the legal system that is the substance of the law, the legal structure, the legal culture in the achievement of the crime of fishery law enforcement effective, ideal and integrative.